Clinical utility of clodronate in the prevention and management of osteoporosis in patients intolerant of oral bisphosphonates - Muratore M; Quarta E; Grimaldi A; Calcagnile F; Quarta L (Dove Medical Press, 2011)
Maurizio Muratore, Eugenio Quarta, Antonella Grimaldi, Fabio Calcagnile, Laura Quarta Department of Rheumatology, Hospital Galateo, San Cesario di Lecce, Italy Abstract: Bisphosphonates have a long history in the treatment of osteoporosis and bone-related disease. This review focuses on the use of a specific nonaminobisphosphonate, clodronate, which appears to be much better tolerated than other bisphosphonates and free of high-risk contraindications. Specifically, this paper reviews its use in the prevention of osteoporosis in postmenopausal women, taking into account its tolerability profile and recent safety issues arising regarding the use of bisphosphonates. Keywords: clodronate, bisphosphonates, osteoporosis, bone turnover, menopause, tolerability